Local planning attitudes: Comparative content analysis of municipal director plans of shrinking Portuguese cities - Sousa Sílvia (Bulletin of Geography. Socio-Economic Series)
Traditional planning practice, in its essence, usually pursues urban growth, and is more comfortable dealing with population increase and other growth dynamics than with population decline and what ensues. The main goal of this article is to assess local planning attitudes in Portugal towards demographic change, and in particular towards population decrease, in terms of housing development. In order to do so, a comparative content analysis of municipal director plans (PDM) – Planos Diretores Municipais – of the fourteen Portuguese cities that shrank prevalently and persistently across both conjoining periods 1991– 2001–2011 was completed using a simple matrix of analysis. The qualitative analysis of the regulations of these PDMs showed that aspects of population decrease and shrinkage in relation to housing development are gradually entering local planning practice, though there is not yet an overall intelligible strategy. In Portugal, demographic change and housing development are only just starting to come together in local spatial planning.